Escherichia coli O157:H7 EDL933 has a strong virulence to Bama miniature pigs by injection and fails to colonize to their gastrointestinal tracts - Honglei Ding,Rui Zhang,Kaiyun Liu,Linping Huang; Maochun Tian; Mingming Jiang , Quanming Zou; Xuhu Mao (African Journal of Pig Farming, 2017)
Detection of Shiga toxin-producing Escherichia coli O157:H7 from commercially grown pigs has been reported. Furthermore, the E. coli O157:H7 colonized model of pig has been established and E. coli O157:H7 could be transmitted from infected donor pigs to naïve pigs directly and indirectly. In the present study, we want to know whether any E. coli O157:H7 strain can colonize to the alimentary tract of pig and the virulence of E. coli O157:H7 to pig by injection. Bama miniature pig was infected with E. coli O157:H7 EDL933 strain orally, but the organism could not be recovered from the feces and did not cause any tissue damage. Nevertheless, this pathogen introduced serious clinical symptoms and pathological injuries by injection, especially the nervous system and the injected pig exhibited severe neurological symptoms, including synclonus tremens, ataxia, head-pressing and recumbency, etc. The pig did not excrete urine and feces and the abdomen became tympanous. These data suggested that only certain E. coli O157:H7 strains could colonize to the GIs of pigs involved mechanisms that related to various factors. However, the organism has strong virulence to pig by injection mode and it is a risky pathogen to human health.